Abnormal rate of human chorionic gonadotropin rise: a case series of patients with viable intrauterine pregnancies after embryo transfer - Lauren Kendall Rauchfuss, M.D; Alessandra J. Ainsworth, M.D; Chandra C. Shenoy, M.D (Elsevier, 2021)
Objective: To report three cases of viable intrauterine pregnancies after embryo transfer with lower quantitative human chorionic gonadotropin (hCG) rates of rise than that expected in 99% of normal intrauterine pregnancies, based on current guidelines. Design: Case series. Setting: Tertiary care center. Patient(s): Three patients underwent in vitro fertilization for ovulatory dysfunction or male factor infertility and had successful live births after an unusually low rate of hCG rise following embryo transfer. Intervention(s): In vitro fertilization was utilized for all three patients. Main Outcome Measure(s): Serial hCG levels. Result(s): Three cases of abnormally rising hCG levels were described. All cases presented achieved pregnancy through assisted reproductive technologies. The lowest documented rate of rise for each case, over 48 hours, was 22.1%, 23.3%, and 26.9%. All three cases resulted in live births. Literature on this topic was reviewed. Conclusion(s): Based on the cases presented, we recommend conservative management for patients found to have abnormally low rise hCG levels after embryo transfer; a high clinical suspicion for ectopic pregnancy should be maintained.